Lipid-Nucleic Acid Complexes: Physicochemical Aspects and Prospects for Cancer Treatment - Ricardo Gaspar; Filipe Coelho; Bruno F. B. Silva (Molecules, 2020)
Cancer is an extremely complex disease, typically caused by mutations in cancer-critical genes. By delivering therapeutic nucleic acids (NAs) to patients, gene therapy offers the possibility to supplement, repair or silence such faulty genes or to stimulate their immune system to fight the disease. While the challenges of gene therapy for cancer are significant, the latter approach (a type of immunotherapy) starts showing promising results in early-stage clinical trials. One important advantage of NA-based cancer therapies over synthetic drugs and protein treatments is the prospect of a more universal approach to designing therapies. Designing NAs with different sequences, for different targets, can be achieved by using the same technologies. This versatility and scalability of NA drug design and production on demand open the way for more efficient, affordable and personalized cancer treatments in the future. However, the delivery of exogenous therapeutic NAs into the patients’ targeted cells is also challenging. Membrane-type lipids exhibiting permanent or transient cationic character have been shown to associate with NAs (anionic), forming nanosized lipid-NA complexes. These complexes form a wide variety of nanostructures, depending on the global formulation composition and properties of the lipids and NAs. Importantly, these different lipid-NA nanostructures interact with cells via different mechanisms and their therapeutic potential can be optimized to promising levels in vitro. The complexes are also highly customizable in terms of surface charge and functionalization to allow a wide range of targeting and smart-release properties. Most importantly, these synthetic particles offer possibilities for scaling-up and affordability for the population at large. Hence, the versatility and scalability of these particles seem ideal to accommodate the versatility that NA therapies offer. While in vivo efficiency of lipid-NA complexes is still poor in most cases, the advances achieved in the last three decades are significant and very recently a lipid-based gene therapy medicine was approved for the first time (for treatment of hereditary transthyretin amyloidosis). Although the path to achieve efficient NA-delivery in cancer therapy is still long and tenuous, these advances set a new hope for more treatments in the future. In this review, we attempt to cover the most important biophysical and physicochemical aspects of non-viral lipid-based gene therapy formulations, with a perspective on future cancer treatments in mind.